A history of the Greek resistance in the Second World War : The people's armies - Tsoutsoumpis, Spyros (Book collections on Project MUSE., 2016)
This book tells the story of the Greek resistance to Axis occupation during the Second World War and in particular the life of armed guerrillas. Rather than provide a conventional military history it will illuminate for the first time the lives, experiences and thoughts of the resistance fighters during their fight against the Occupation.